1997
DOI: 10.1136/jech.51.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Hazard proximities of childhood cancers in Great Britain from 1953-80.

Abstract: Study objectives -Firstly, to examine relationships between the birth and death addresses of children dying from leukaemia and cancer in Great Britain, and the sites of potential environmental hazards; and secondly to measure relative case densities close to, and at increasing distances from, different hazard types. Design -Home address postcodes (PCs) and their map coordinates were identified at birth and at death in children who died from leukaemia or cancer. Potentially hazardous industrial addresses and PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 16 publications
1
68
2
Order By: Relevance
“…Muirhead (1995) (1990) who estimated that up to 15% of childhood cancers could be attributed to an average radon exposure of 50 Bq m-3. At these levels of exposure, the proportion of cases likely to be due to radon exposure is similar to that associated with childhood cancer risk after irradiation of the fetus in utero by radiography of the abdomen of the pregnant mother (Stewart et al, 1958;Bithell and Stewart, 1975;Muirhead and Kneale, 1989 (Knox and Gilman, 1997). The apparent inconsistency of our present findings is possibly because of the inability of analysis at the larger scale of 10-km squares to detect the short-range effects of local discrete hazards.…”
Section: Discussioncontrasting
confidence: 56%
“…Muirhead (1995) (1990) who estimated that up to 15% of childhood cancers could be attributed to an average radon exposure of 50 Bq m-3. At these levels of exposure, the proportion of cases likely to be due to radon exposure is similar to that associated with childhood cancer risk after irradiation of the fetus in utero by radiography of the abdomen of the pregnant mother (Stewart et al, 1958;Bithell and Stewart, 1975;Muirhead and Kneale, 1989 (Knox and Gilman, 1997). The apparent inconsistency of our present findings is possibly because of the inability of analysis at the larger scale of 10-km squares to detect the short-range effects of local discrete hazards.…”
Section: Discussioncontrasting
confidence: 56%
“…Elevated risks of childhood cancer were associated with several surrogate measures of vehicle exhaust exposure, including traffic volume, car density, estimated concentration of nitrogen dioxide in outdoor air and proximity to sources of vehicle exhaust (Savitz and Feingold, 1989;Knox and Gilman, 1997;Nordlinder and Jarvholm, 1997;Feychting et al, 1998;Harrison et al, 1999;Pearson et al, 2000). Recent studies in California evaluating childhood cancer and traffic density have generally found no association (Reynolds et al, 2001;Langholz et al, 2002;Reynolds et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Continuous long-term exposure to low environmental concentrations of benzene is an issue of special public health concern, as several investigations so far reported positive associations between residence near potential hydrocarbon emission sources (e.g., oil raffineries) or indicators of automotive emissions and acute childhood leukaemia (Knox, 1994;Lyons et al, 1995;Sans et al, 1995;Knox and Gilman, 1997;Harrison et al, 1999;Wilkinson et al, 1999). Moreover, five out of six case-control studies showed a positive association between different indicators of air pollution or heavy traffic in the vicinity of children's homes and acute leukaemia (Savitz and Feingold, 1989;Nordlinder and Jarvholm, 1997;Feychting et al, 1998;Harrison et al, 1999;Pearson et al, 2000;Raaschou-Nielsen et al, 2001;Langholz et al, 2002;Crosignani et al, 2004), whereas in three of these studies, this association turned out to be significant (Nordlinder and Jarvholm, 1997;Pearson et al, 2000;Crosignani et al, 2004).…”
Section: Introductionmentioning
confidence: 99%